A STUDY OF PATIENT’S MONETARY SATISFACTION AT A PRIVATE HOSPITAL IN NAGPUR - Choube, Santosh Kumar; Ladha, Namrata; Papne, Nidhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Before any surgery or clinical procedure takes place, estimates are given to make patient understand that how much they need to spend on a particular procedure (surgery) because if in case there is any fluctuation in the actual bills, it will ultimately lead to patients’ dissatisfaction. The proposed study is quantitative by the nature due to primary and secondary databases used to analyze the estimated and actuals bills of the CABG and PTCA patients in the wockhardt heart hospital, Nagpur. The design for the research is exploratory and descriptive as the patient’s bill have been compared to check whether there is any difference exist or not. The study analyzes the factors responsible for creating differences between the estimated and actual bills and suggests measures that will help in reducing the differences in the estimates and actual bills.